Inclusive audiovisual educational tools: design and application - Angela Cristina Yánez Corrales; Verónica Elizabeth Espinosa Echeverria; Daniela Cárdenas Pérez (Medisur)
Background: to achieve that people with special educational needs are trained on the basis of merit, their own abilities, effort, perseverance and above all that they take into account their potential, is a challenge. Objective: design accessible videos for students, including those with special educational needs, as well as evaluate their applicability. Methods: videos and their application were designed based on the Technological Pedagogical and Content Knowledge theoretical model: curricular knowledge, pedagogical knowledge and technological knowledge, with emphasis on adaptation to special educational needs to facilitate learning. The evaluation considered the application of the instrument "Evaluation of audiovisual educational tools" from the parameters: attention, curiosity, usefulness in review, stimulus to learn, help to understand and the desire to reuse them. Results: three videos were designed with accessibility elements for students, including students with special educational needs. In the evaluation, it was achieved, in a general way, the qualification increase in the partial tests of the subject after the use of the videos; the use’s perception determined the satisfaction as a learning resource. Conclusions: the design of accessible audiovisual resources without difference with students with disabilities, benefits the entire group of students, within the equality framework.